The present and future of psychosocial therapy for vulnerable people in Spain. The contribution of mobile phones - Garcia Vazquez, Yolanda; Ferrás, Carlos; Aguilera, Adrián; Rocha, Alvaro (Cuadernos de Trabajo Social, 2018)
We analyse international academic literature focused on mobile phones and psychosocial therapies. We identify articles published between 2000 and 2015 and available on Internet databases; and we highlight the scarce number of investigations focusing on vulnerable people. Literature specializing in psychosocial therapies address the usefulness of mobile phones in patients in general, with greater production from psychology and to a lesser extent from social work. We highlight the research developed in the USA and its residualness in Spain, where debates focus on the competences of the social worker in this field. We identify opportunities and limitations in terms of data privacy, access to and use of mobile phones; to reach isolated or poor populations or to facilitate access to social and health services. We conclude with possible orientations, hypotheses and goals for prospective investigation works.